Comparison of magnetic resonance imaging and high frequency ultrasonography in carcinoma of tongue and its clinicopathological correlation: a prospective study - Mir, Javed A.; Masoodi, Sanober M.; Rashid, Tajamul; Masoodi, Suhail M. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Carcinoma of oral tongue has a high propensity for cervical node metastasis. The thicker the tumour, the higher would be the risk of nodal metastasis and locoregional recurrence. Ultrasonography is used for evaluation of carcinoma tongue and tumour thickness and has a high correlation with histopathological findings. Methods: Our study is a comparative prospective study conducted on 30 patients of carcinoma tongue. All patients underwent magnetic resonance imaging (MRI) scan and ultrasonography. The findings of MRI and ultrasound were correlated with clinical and pathological findings. Results: MRI had a better correlation with histopathology for primary tumour characteristics and nodal assessment than ultrasonography. Ultrasound with a Pearson correlation coefficient of 0.809 correlated better than MRI for tumour thickness. Tumour thickness of >5 mm was associated with 27.2% nodal positivity rate whereas no patient with primary tumour thickness <5 mm had node positive disease. Conclusions: Ultrasonography has a high correlation with histopathological thickness. Ultrasound thus seems to be an optimal technique in early stage, node negative tongue cancer for evaluation of tumour thickness and predict nodal status.